Evaluation of The Business Performance of PT ADARO Energy Indonesia Tbk Before and After Business Diversification With A Competitive Intelligence Approach - Hotman Auditua; Palupi Lindiasari Samputra (Pelopor Publikasi Akademika, 2025)
This research examines the impact of business diversification on the financial performance of PT Adaro Energi Indonesia Tbk (ADRO) in response to Indonesia's high dependence on coal, which poses long-term risks related to resource limitations and sustainability challenges. The study aims to analyze ADRO’s financial performance before and after diversification, particularly its transition into clean water processing, solar power, hydropower, and steam power plants. Using a quantitative descriptive method, this research utilizes financial report data from 2015 to 2023 to assess key financial indicators such as Return on Equity (ROE), Return on Assets (ROA), liquidity, and equity growth. The findings indicate that before diversification (2015–2017), ADRO exhibited stable financial performance, with an ROE of 13.1% and an ROA of 7.9% in 2017, alongside a Current Ratio of 2.6 and equity growth to USD 4,091,627 thousand. Post-diversification (2018–2023), the company showed significant improvement, achieving a peak ROE of 43.4% in 2022, strengthened liquidity, and enhanced asset and equity value. The results suggest that business diversification has positively impacted ADRO by reducing dependence on coal, expanding into renewable energy sectors, and enhancing long-term financial sustainability.